The Effect Of Tax Examination Effectiveness On Tax Avoidance With Political Connection Moderation - Roshid Andru Mustaqiim; Nurhidayati Nurhidayati (Riset: Jurnal Aplikasi Ekonomi Akuntansi dan Bisnis, 2020)
The self-assessment system in which the taxpayer performs the calculation, payment, and tax reporting by the taxpayer itself risks tax avoidance practices. To minimize this risk, the Directorate General of Taxation carries out law enforcement in the framework of supervision through tax audit activities. This study aims to analyze the effect of the effectiveness of the inspection on tax avoidance practices by using a moderated political connection because it is suspected that companies with a political link tend to be more aggressive in terms of tax planning. This study uses panel data of companies listed on the Indonesia Stock Exchange from 2016 to 2018. The study results conclude that tax audits effectiveness has a significant effect on tax avoidance practices, which means that the more influential the tax audit activities are, the lower the tax avoidance level.